Lagenidium sp. infection in the larval stages of the freshwater prawn Macrobrachium rosenbergii (DeMan) - Krishnika, A.; Ramasamy, P. (Indian Journal of Fisheries, 2014)
This study investigated the occurrence, infectivity and pathogenecity of Lagenidium sp. in the hatchery of Macrobrachium rosenbergii. Microscopic examination revealed that the Lagenidium sp. infected zoea appeared white in colour. The presence of non-septate fungal hyphae was observed within the body of the exposed larvae replacing nearly all the muscles. Light and scanning electron microscopy demonstrated that 24 h post-exposure, the infection began to appear externally. After 32 h, zoospores appeared on external hyphae of infected larvae. The fungus Lagenidium sp. exhibited optimum growth at 30 0C, 0-2% NaCl and slow growth at 5% NaCl on potato dextrose agar (PDA). Antimicrobials, clotrimazole and griseofulvin were found to be more effective than miconazole, itraconazole and fluconazole in inhibiting the growth of Lagenidium sp. Under experimental conditions, Lagenidium sp. causes 100% mortality within two days of infection, producing 103 spores ml-1,